C–F Bond Functionalization with Organolithium Compounds - Bouda, Maria; Lucas Kane, D.; Figula, Bryan C.; Xhili, Dea; Hana, Grace E.; Bertke, Jeffery A.; Wolf, Christian (Synthesis, 2025)
Cross-coupling of alkyl fluorides and organolithium compounds is achieved by liquid-assisted stirring and mild heating without the need for expensive catalysts or additives. The reaction proceeds with a variety of primary, secondary, and tertiary fluorides; several functional groups, including alkyl halides, ether, amide, and heteroaryl groups, are tolerated; and both aryl and alkyllithium compounds can be used. Mechanistic studies indicate that the reaction involves heterolytic C–F bond activation and proceeds either via generation of short-lived carbocation intermediates or through a concerted pathway, which probably predominates with primary substrates, while the formation of thermodynamically stable lithium fluoride is the driving force.
Keywords: Alkyl fluorides; Cross-coupling; Organolithium reagents; C–F bond functionalization; Liquid-assisted mixing